Modeling and Control of Adjustable Articulated Parallel Compliant Actuation Arrangements in Articulated Robots - Roozing, Wesley (Frontiers in Robotics and AI, 2018)
Considerable advances in robotic actuation technology have been made in recent years. Particularly the use of compliance has increased, both as series elastic elements as well as in parallel to the main actuation drives. This work focuses on the model formulation and control of compliant actuation structures including multiple branches and multiarticulation, and significantly contributes by proposing an elegant modular formulation that describes the energy exchange between the compliant elements and articulated multibody robot dynamics using the concept of power flows, and a single matrix that describes the entire actuation topology. Using this formulation, a novel gradient descent based control law is derived for torque control of compliant actuation structures with adjustable pretension, with proven convexity for arbitrary actuation topologies. Extensions toward handling unidirectionality of elastic elements and joint motion compensation are also presented. A simulation study is performed on a 3-DoF leg model, where series-elastic main drives are augmented by parallel elastic tendons with adjustable pretension. Two actuation topologies are considered, one of which includes a biarticulated tendon. The data demonstrate the effectiveness of the proposed modeling and control methods. Furthermore, it is shown the biarticulated topology provides significant benefits over the monoarticulated arrangement.